Introligatorstwo w Bydgoszczy w świetle dokumentacji egzaminów zawodowych z lat 1901-1933 (Kronika Bydgoska, 2012)
At the State Archive in Bydgoszcz, in the group of files of the Chamber of Craftsmanship, there are documents of bookbinder examinations. The examinations were characterised by a fairly high level of difficulty. A significant part of candidates had difficulties and took the examination several times. The examinations included a practical part, i.e. performance of a specific bookbinding work, and a theoretical part. While the owners of bookbinding companies in Bydgoszcz were almost exclusively Germans, Poles were 2/5 among the bookbinding students. After World War One, the examination board continued the operations in a changed make up, butwithin the same organisational stractures; all candidates were Poles. Master examinations became less important at that time, and few applicants sat for the examination. The group of bookbinding masters participating in the works of the examination board was also the hard core of the Bookbinders’ Guild established in 1907, and chairman Arthur Huch became the Guild’s Head. Information obtained from the archive files, address publications, an analysis of the storehouse resources of the Voivodeship and Municipal Public Library in Bydgoszcz, and from other sources make it possible to outline the figures of some bookbinders from Bydgoszcz: Huch, Leopold, Groch, Grabowski, Spudich, Franke, Jankę, and Ciszewski. It was also possible to track the fate of several bookbinding students passing the examinations before the Bydgoszcz examination board.